2012
DOI: 10.1159/000341615
|View full text |Cite|
|
Sign up to set email alerts
|

Decrease in Incidence of Bronchopulmonary Dysplasia with Erythropoietin Administration in Preterm Infants: A Retrospective Study

Abstract: Background: Despite advances in clinical care, the incidence of bronchopulmonary dysplasia (BPD) remains high in premature infants. Erythropoietin (EPO) is used for the treatment of anemia of prematurity (AOP) to decrease blood transfusion needs. EPO has been shown to mobilize circulating endothelial progenitor cells and to enhance lung repair in animal models. Objective: To determine whether EPO treatment for AOP was associated with a reduced incidence of BPD in premature infants. Methods: This retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
22
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
(32 reference statements)
5
22
0
4
Order By: Relevance
“…Interestingly, data from our own unit provides support for the observations of Rayjada et al [1]. Between 2000 and 2007, we routinely used EPO in infants <28 weeks.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, data from our own unit provides support for the observations of Rayjada et al [1]. Between 2000 and 2007, we routinely used EPO in infants <28 weeks.…”
supporting
confidence: 83%
“…The observational study by Rayjada et al [1] demonstrated a reduction in bronchopulmonary dysplasia (BPD) in infants receiving erythropoietin (EPO). The study included a relatively large number of preterm infants at a single institution, presumably reducing inconsistency in terms of issues such as diagnosis of BPD.…”
mentioning
confidence: 99%
“…In preterm infants, neonatal rh-EPO drug treatment is associated with a decreased incidence of BPD,23 24 and a reduction of length of ventilation support 24. A protective effect of rh-EPO is also suggested in NEC pathogenesis where EPO enhanced the cell-cell barriers in epithelial cells in rats,25 and a lower incidence of NEC has been observed in newborns receiving rh-EPO 26.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that EPO has many unexpected nonhematopoietic functions, including reducing the incidence of bronchopulmonary dysplasia [6], neuroprotection and angiogenesis [7]. Results of studies on injured prenatal brains have shown that neonatal rh-EPO administration is beneficial to myelination [8], rescues neural cells and induces lasting histological and functional improvements [9].…”
Section: Introductionmentioning
confidence: 99%